Catheter ablation of concomitant atrial fibrillation improves survival of patients undergoing transcatheter edge-to-edge mitral valve repair - Ausbuettel, Felix; Barth, Sebastian; Chatzis, Georgios; Fischer, Dieter; Kerber, Sebastian; Mueller, Julian; List, Stephan; Halbfass, Philipp; Deneke, Thomas; Nef, Holger; Mueller, Hans-Helge; Divchev, Dimitar; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Atrial fibrillation (AF) is the most common concomitant disease in patients undergoing transcatheter edge-to-edge repair (TEER) for mitral regurgitation (MR) and detrimentally affects their outcome. While there is increasing evidence for prognostic improvement and safety of catheter ablation (CA) of AF in the overall cohort of heart failure patients, corresponding data in TEER patients are lacking. Objectives To investigate the impact of treatment regimens for concomitant AF on survival of TEER patients. Methods In a multicenter observational cohort study consecutive patients successfully undergoing TEER were analyzed and survival of patients receiving CA of concomitant AF was compared with that of patients on pharmacological AF treatment and with that of patients without a history of AF, using propensity score matching (PSM). Results A total of 821 patients were analyzed. Of these, 608 (74.1%) had concomitant AF, of whom 48 patients received CA. Patients with CA in AF showed significantly higher 3-year-survival after TEER compared to PSM-patients on pharmacological AF treatment (75.5% [36/48] vs. 49.4% [166/336], p = 0.009). The 3-year-survival after TEER of patients with concomitant AF treated with CA was not significantly different from PSM-patients without AF (75.5% [36/48] vs. 68.3% [98/144], p = 0.36). Conclusions CA of AF is superior to pharmacotherapy as it significantly improves the survival of TEER patients in a PSM analysis. CA even offsets the prognostic disadvantage of coexisting AF in TEER patients. Given the growing evidence of prognostic benefits in the overall cohort of HF patients, our data point out the importance of treating concomitant AF and support CA as an essential part of a holistic management of TEER patients.